Philosophy, Religion, Art as a Hermeneutical Discourse - Svičiulienė, Jūratė (Respectus Philologicus, 2006)
The article highlights the relevance of cultural studies, revealing ontological links of substantive cultural phenomena. Since hermeneutic discourse is particularly popular in culturology, the main categories of W. Dilthy’s "philosophy of life" that refer to his hermeneutical method are also widely discussed. By tradition, the peculiarity of philosophical thinking is based on a comparison of philosophy and other cultural spheres - mythology, religion, art and science. Dilthy has the same approach; thus, his research of relations between philosophy, religion and poetic culture is the basis of this work, expanding the limits of "romantic" or classical problem of interpretation and understanding. Further, a conclusion about the cohesion between philosophy, religion, art and their various forms of expression is also formulated.